Mycobiota in Mycobiota in the grain of the oat breeding lines produced in 2019 in competitive variety trials on the fields of Nemchinovka Federal Research Center, Moscow Provincepetitive variety trials on the fields of Nemchinovka Federal Research Center, Moscow Province - O. P. Gavrilova; T. Yu. Gagkaeva; A. S. Orina; A. S. Markova; A. D. Kabashov; I. G. Loskutov (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. The requirement for high-quality oat grain for food production leads to the need for studying the resistance of this cereal crop to harmful diseases and for the development of new productive cultivars.Materials and methods. A comparative characterization was performed among the breeding lines of naked oats from Nemchinovka Federal Research Center according to the parameters of microbiological purity of grain. The mycological method was applied for the analysis of infection in the oat grain, and fungal species composition was identified. The DNA amount of toxin-producing species from genus Fusarium Link in the grain was detected using the real-time PCR, and the amount of mycotoxins was measured by the enzyme immunoassay.Results. The fungi of Alternaria Nees, Fusarium, Cladosporium Link, Cochliobolus Drechsler, Epicoccum Link were associated with oat grain. Uniquely high infection of the grain by F. langsethiae Torp & Nirenberg (14%) was found under the natural conditions of the Central Region of Russia. The differences revealed among the analyzed breeding lines and cultivars in the DNA amount of F. langsethiae and F. sporotrichioides Sherb. were from 1.3×10-4 to 7.2×10-3 pg/ng in the total DNA, and from 5 to 1230 μg/kg in the content of T-2/ HT-2 toxins.Conclusion. All naked oat breeding lines were relatively resistant to Fusarium infection and proved the best as regards the mycotoxin contamination of the grain against the reference hulled cultivar ‘Yakov’. In the competitive variety trials, three lines – 66h2618, 54h2476 and 70h2613 – were characterized as relatively resistant to Fusarium disease, compared with the naked oat reference ‘Vyatsky golozerny’.